Pengaruh Posisi Penyinaran Radiasi Berkas Foton di Titik Axis dan Tepi Lapangan Terhadap Dosis Serap pada Pesawat Linac - Nur Alya; Robert Janssen Stevenly; Pratiwi Sri Wardani; Erlinda Ratnasari Putri (Jurnal Inotera, 2024)
Radiotherapy is a medical treatment that uses ionizing radiation to kill cancer cells using a Linear Accelerator (Linac). One of the errors in radiotherapy irradiation can occur because the radiation beam that comes out is not in accordance with the planning. Therefore, radiation absorbed dose measurement is needed to carry out as a quality assurance to control the accuracy and suitability of the dose to be received by the patient by following the standards of the Technical Report Series (TRS) 398. This study was conducted at Radiotherapy Installation of RSUD A.W. Sjahranie Samarinda. In the measurement of radiation absorbed dose, the detector was placed in the center of the water phantom with a certain depth and placed in an axis position perpendicular to the radiation source. The detector is not only placed in the axis position, but also placed on the 4 edges of the field with the aim of knowing the effect of the location of the detector on the absorbed dose on the Linac plane. Medium water phantom, Farmer type ionization detector with a depth of 10 cm, and radiation source distance to the phantom surface of 100 cm were applied in this study. The measurement deviation results at the axis position and 4 field edges are 0.01%, 0.06%, 0.03%, 0.05%, and 0.05%. These values are within the tolerance limits written in the IAEA TRS 398 protocol, which is ± 2%. This states that the radiation absorbed dose by the water phantom is homogeneous in all directions.